2010
DOI: 10.1177/1078087410379720
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Up Without Clearing Out? A Spatial Assessment of Environmental Gentrification

Abstract: The environmental gentrification hypothesis predicts that environmental quality improvements in poor communities may spur gentrification and the displacement of residents. The author analyzes the relationship between hazardous site cleanups and gentrification in Portland, Oregon, during the 1990s. Using resident-defined neighborhoods as the unit of analysis, the author finds that there is no relationship between the extent of gentrification a neighborhood experiences and the perceived or actual environmental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 46 publications
(77 reference statements)
3
42
0
1
Order By: Relevance
“…The conventional thesis in the relatively new literature on environmental gentrification "predicts that environmental quality improvement in poor communities may spur gentrification and the displacement of residents" [51]. Our research supports a different, and more complex process.…”
Section: Environmental Gentrification and The Post-industrial Citysupporting
confidence: 55%
See 1 more Smart Citation
“…The conventional thesis in the relatively new literature on environmental gentrification "predicts that environmental quality improvement in poor communities may spur gentrification and the displacement of residents" [51]. Our research supports a different, and more complex process.…”
Section: Environmental Gentrification and The Post-industrial Citysupporting
confidence: 55%
“…Our Seattle case study contributes to the more recent scholarly attention to environmental gentrification [47][48][49][50][51][52][53][54][55]. Banzhaf and Walsh were some of the first that pondered how "in a world where households sort in response to changes in environmental quality, the bulk of the benefits of a policy that successfully cleans up dirtier neighbourhoods where the poor live may actually be captured by rich households...…”
Section: Environmental Inequities and Gentrificationmentioning
confidence: 99%
“…This is not to say, in a normative sense, that tree planting efforts are always good, and cannot be coopted or commenced for other less desirable purposes, especially in time of great upheaval such as disasters or war (see earlier reference to Braverman 2009). There is a large and growing literature that makes disturbing connections between "greening" activities such as tree planting and gentrification and/ or displacement (see for example Checker 2011, Eckerd 2011, Gould and Lewis 2012, Sandberg 2014. Though from an environmental justice perspective this outcome is to be avoided at all costs, an unfortunate consequence of this thinking is that creation of new boundaries between humans, especially of a certain class or ethnicity, and the rest of the social-ecological systems within which we reside, perhaps unwittingly, reinforces the most poisonous dichotomy of all, that humans are separate from so-called nature (Harvey 1997, Castree andBraun 2001).…”
Section: Discussionmentioning
confidence: 99%
“…But efforts to re-green cities, especially in lowincome and so-called minority neighborhoods can have paradoxical consequences. For instance, researchers have shown that the development of parks and other greenspaces can increase property values (Eckerd 2011). Unless efforts are taken to manage this effect, it can eventually result in the displacement of marginalized and vulnerable people (Pearsall 2012).…”
Section: Political Ecology(ies) Of Just Urban Greenspacementioning
confidence: 99%
“…Recently, some researchers have observed that urban greening can trigger 'environmental-gentrification', further entrenching environmental inequalities (Checker 2011, Eckerd 2011, Kern 2015, Pearsall 2010). Environmental-gentrification occurs when the conversion of brownfields to greenspace, provision of new greenspace, or redevelopment of existing greenspace drives-up property values, because a location becomes more attractive to investors and/or more desirable for residents (Millington 2015, Quastel 2009).…”
Section: Introductionmentioning
confidence: 99%